1995
DOI: 10.1126/science.270.5241.1488
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Checkpoint Genes in DNA Damage Processing: Implications for Repair and Arrest

Abstract: Yeast checkpoint control genes were found to affect processing of DNA damage as well as cell cycle arrest. An assay that measures DNA damage processing in vivo showed that the checkpoint genes RAD17, RAD24, and MEC3 activated an exonuclease that degrades DNA. The degradation is probably a direct consequence of checkpoint protein function, because RAD17 encodes a putative 3'-5' DNA exonuclease. Another checkpoint gene, RAD9, had a different role: It inhibited the degradation by RAD17, RAD24, and MEC3. A model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
379
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(403 citation statements)
references
References 26 publications
(4 reference statements)
23
379
1
Order By: Relevance
“…It is still not known whether there exist discrete but overlapping regulatory pathways triggered separately by unreplicated DNA and by DNA damage or whether genes such as the RAD9 group are simply additionally required to activate the DNA damage checkpoint in an otherwise identical signal transduction pathway. It has been shown that RAD9, MEC3, RAD24, and RAD17 play a role in processing DNA lesions and therefore could be involved in generating the signal to activate the checkpoint at G~/S and G2/M (Lydall and Weinert 1995). However, it was not shown whether the effect on DNA processing was directly attributable to these proteins or attributable to defects in signaling that occur in these mutants.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…It is still not known whether there exist discrete but overlapping regulatory pathways triggered separately by unreplicated DNA and by DNA damage or whether genes such as the RAD9 group are simply additionally required to activate the DNA damage checkpoint in an otherwise identical signal transduction pathway. It has been shown that RAD9, MEC3, RAD24, and RAD17 play a role in processing DNA lesions and therefore could be involved in generating the signal to activate the checkpoint at G~/S and G2/M (Lydall and Weinert 1995). However, it was not shown whether the effect on DNA processing was directly attributable to these proteins or attributable to defects in signaling that occur in these mutants.…”
mentioning
confidence: 79%
“…Recently, RAD9, RAD17, RAD24, and MEC3 have been postulated to be involved in processing cdcl3-induced lesions near the telomeres (Garvik et al 1995;Lydall and Weinert 1995). Although RAD9 was shown to act differently from RAD24, MEC3, and RAD17 in processing DNA damage, all four genes appear to act in the same pathway with respect to cell-cycle arrest and would be expected to have phenotypes similar to rad9 mutants in the RNR3 transcription assay.…”
Section: Transcriptional Response Of Other Checkpoint Mutants Shows Rmentioning
confidence: 99%
“…Rad1 sp is similar to the Ustilago Rec1 exonuclease, the putative human Rad1 sp homolog (hRad1) displays exonuclease activity [15,16•], and Rad17 sp has limited similarity to replication factor C (RFC) [17]. Furthermore, S. cerevisiae homologs of Rad1 and Rad17 have been implicated in the processing of DNA damage [18]. The most interesting similarity is that of Rad3 sp to DNA-dependent protein kinase (DNA-PK) [19,20].…”
Section: The Schizosaccharomyces Pombe G 2 Dna Damage Checkpointmentioning
confidence: 99%
“…Several proteins of the Rad24 sc group are structurally similar to proteins involved in DNA metabolism (Table 1), and are required for the processing of damaged DNA [18]. Both Rad9 sc and Ddc1 sc , however, are phosphorylated after DNA damage in a Mec1 sc dependent manner, indicating that they lie downstream of Mec1 sc [45••,51•,57••].…”
Section: The Schizosaccharomyces Pombe G 2 Dna Damage Checkpointmentioning
confidence: 99%
“…The DNA damage checkpoint signal is generated in response to ssDNA detection by the ATR-ATRIP and 9-1-1 complexes (Lydall and Weinert 1995;Melo et al 2001;Zou and Elledge 2003). The DNA damage checkpoint has been shown to be required for efficient DSB repair where Rad24 Sc is required for resection and, thus, ssDNA production (Aylon and Kupiec 2003), while Rad9 Sc has been shown to limit ssDNA production associated with DSB repair (Lazzaro et al 2008).…”
Section: Checkpoint-dependent Ssdna Regulation and Dsb Repairmentioning
confidence: 99%